2021
DOI: 10.1002/admt.202101371
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Stretchable and Tough Piezoelectric Gels for Artificial Electronic Skin

Abstract: Piezoelectric sensors and energy harvesters have received considerable interest due to their self‐powered capability and potential applications in various electronic devices. However, it is still a challenge to fabricate stretchable piezoelectric devices because piezoelectrics mainly consists of stiff crystalline structures. Here, extremely stretchable and tough piezoelectric gels are reported, which are prepared simply by swelling poly(ethylene glycol) (PEG)‐based poly(urethane‐urea) (PUU) gels with aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…[5][6][7][8] An efficient e-skin design requires a combination of functional materials with suitable mechanical and electrical properties, [9] in addition to the micro/nanoscale control of the layer's thickness and dimensions, which is optimized by the choice of suitable fabrication techniques.For pressure and force detection, the most common methods exploit piezoelectric, piezoresistive, or capacitive sensing. [10][11][12][13] Bao's group investigated an e-skin design based on flexible pressure-sensitive organic thinfilm transistors deploying a force-sensitive gate dielectric capacitance. The sensor has a maximum sensitivity of 8.4 kPa −1 and a fast response time of 10 ms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] An efficient e-skin design requires a combination of functional materials with suitable mechanical and electrical properties, [9] in addition to the micro/nanoscale control of the layer's thickness and dimensions, which is optimized by the choice of suitable fabrication techniques.For pressure and force detection, the most common methods exploit piezoelectric, piezoresistive, or capacitive sensing. [10][11][12][13] Bao's group investigated an e-skin design based on flexible pressure-sensitive organic thinfilm transistors deploying a force-sensitive gate dielectric capacitance. The sensor has a maximum sensitivity of 8.4 kPa −1 and a fast response time of 10 ms.…”
mentioning
confidence: 99%
“…For pressure and force detection, the most common methods exploit piezoelectric, piezoresistive, or capacitive sensing. [10][11][12][13] Bao's group investigated an e-skin design based on flexible pressure-sensitive organic thinfilm transistors deploying a force-sensitive gate dielectric capacitance. The sensor has a maximum sensitivity of 8.4 kPa −1 and a fast response time of 10 ms.…”
mentioning
confidence: 99%
“…For instance, the PUU-DH PiezoGel showed several prototype applications of LED lighting, object deformation detection and human motion detection demonstrating the potential uses in self-powered, wearable and artificial e-skin applications. 356 It is interesting to note that in another study, a piezoelectric hydrogel derived from ferroelectric PAN-PVDF revealed excellent piezoelectric coefficient (d 33 , 30 pC N À1 ), skin-like Young's modulus values (1.33-4.24 MPa), good stretchability (90-175%) and high toughness (1.23 MJ m À2 ), indicating it as a promising material for artificial e-skin applications. 266 Moreover, the PiezoGel-based pressure sensor was shown to be capable of detecting physiological signals such as gestures, pulses, and spoken words.…”
Section: Powering Electronicsmentioning
confidence: 91%
“…Stretchable and/or shape adaptable 41 [53,79,126,130,158, Ultrathin d) 5 [183,190,205,210,213] Transparent 9 [130,158,182,187,194,196,203,206,213] Sweat permeable 1 [213] Wireless connected 5 [208,[214][215][216][217] Low-cost 11 [179,183,188,190,191,198,199,204,211,214,218] Facile manufacturing 6 [179,183,184,188,199,214] Biocompatible 4 [53,79,190,213] Metal-free 1 [219] Humidity resistive 2 [181,220] Self-healable 5…”
Section: Hmimentioning
confidence: 99%